Adsorption of Pb(II) from aqueous solution using alkaline-treated natural zeolite: Process optimization analysis - N.A.S., El-Arish; R.S.R., Mohd Zaki; S.N., Miskan; H. D., Setiabudi; N.F., Jaafar (Elsevier, 2022)
Alkaline-treated natural zeolite was prepared by sodium hydroxide treatment of natural zeolite and applied in the adsorption of Pb(II). The response surface methodology (RSM) analysis was conducted under manipulated variables of initial concentration (X1 = 50–400 mg/L), pH (X2 = 2–10), and adsorbent dosage (X3 = 0.5–5.0 g/L). The optimal condition was attained at X1 = 240 mg/L, X2 = 6, and X3 = 1.07 g/L, with Pb(II) removal of 60.75 %. The characterization of alkaline-treated natural zeolite of fresh and spent confirmed the adsorption of Pb(II) onto alkaline-treated natural zeolite. The reusability and regeneration experiments revealed the ability of the alkaline-treated natural zeolite in multiple cycles of the adsorption process. This study proved that alkaline-treated natural zeolite could be an alternative low-cost adsorbent for wastewater treatment containing Pb(II).